2012
DOI: 10.1158/0008-5472.can-12-0010
|View full text |Cite
|
Sign up to set email alerts
|

An Insertion/Deletion Polymorphism within RERT-lncRNA Modulates Hepatocellular Carcinoma Risk

Abstract: The Prolyl hydroxylase 1 (EGLN2) is known to affect tumorigenesis by regulating the degradation of hypoxiainducible factor. Polymorphisms in EGLN2 may facilitate cancer cell survival under hypoxic conditions and directly associate with cancer susceptibility. Here, we examined the contribution of a 4-bp insertion/deletion polymorphism (rs10680577) within the distal promoter of EGLN2 to the risk of hepatocelluar carcinoma (HCC) in Chinese populations. The contribution of rs10680577 to HCC risk was investigated i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…Moreover, affecting apoptosis by DNMT, ABCG2 and TSA also PRKACB, CREB and MLL has been identified in HCC [25,35,[39][40][41][42][43][44][45][46][47][48][49][50][51]. In addition, there is evidence that lncRNAs have important roles in promoting metastasis by targeting factors such as HOXD, VEGF, MMP-9, PRC2, H3K27, RBM38, caspase-3/-8, Bax, Bcl-2, BclxL, ZEB, and IL-11 [23,33,[52][53][54][55][56]. Moreover, lncRNA can inhibit angiogenesis by targeting PGK1 [13,57].…”
Section: Functions and Pathways Involving Lncrnas Targetsmentioning
confidence: 99%
“…Moreover, affecting apoptosis by DNMT, ABCG2 and TSA also PRKACB, CREB and MLL has been identified in HCC [25,35,[39][40][41][42][43][44][45][46][47][48][49][50][51]. In addition, there is evidence that lncRNAs have important roles in promoting metastasis by targeting factors such as HOXD, VEGF, MMP-9, PRC2, H3K27, RBM38, caspase-3/-8, Bax, Bcl-2, BclxL, ZEB, and IL-11 [23,33,[52][53][54][55][56]. Moreover, lncRNA can inhibit angiogenesis by targeting PGK1 [13,57].…”
Section: Functions and Pathways Involving Lncrnas Targetsmentioning
confidence: 99%
“…71 The G allele of rs6983267, in addition to being related to a significantly increased risk of CRC, 72 results in more CCAT2 transcripts than the T allele, which further affects the regulation of MYC by CCAT2; thus different rs6983267 alleles can affect CCAT2 expression and function. 58 Studies examining other cancer types have shown that SNPs in the key regulatory regions of an lncRNA can alter its structural motifs 73 and may consequently affect its expression and function in malignancies, 74 additionally contributing to cancer risk. 75,76 SNPs in the cancer-associated lncRNAs could potentially have pivotal roles in colorectal tumorigenesis and progression.…”
Section: Regulation Of Lncrna Expressionmentioning
confidence: 99%
“…GTP-binding protein 4b and EGLN2) (34). Subsequently, they proved using the Open Reading Frame (ORF) Finder and codon substitution frequency analysis that the overexpressed lncRNA, MVIH, in hepatocellular carcinoma (HCC) is a noncoding RNA transcribed independently of the RPS24 gene and that no correlation existed between the transcriptional levels of RPS24 and MVIH (33).…”
mentioning
confidence: 99%